Effects of repeated long‐term psychosocial stress and acute cannabinoid exposure on mouse corticostriatal circuitries: Implications for neuropsychiatric disorders. (31st January 2018) - Tomas‐Roig, Jordi; Piscitelli, Fabiana; Gil, Vanesa; Quintana, Ester; Ramió‐Torrentà, Lluís l.; del Río, Jose Antonio; Moore, Timothy Patrick; Agbemenyah, Hope; Salinas, Gabriela; Pommerenke, Claudia; Lorenzen, Stephan; Beißbarth, Tim; et al.
Summary: Introduction: Vulnerability to psychiatric manifestations is achieved by the influence of genetic and environment including stress and cannabis consumption. Here, we used a psychosocial stress model based on resident‐intruder confrontations to study the brain corticostriatal‐function, since deregulation of corticostriatal circuitries has been reported in many psychiatric disorders. CB1 receptors are widely expressed in the central nervous system and particularly, in both cortex and striatum brain structures. Aims and methods: The investigation presented here is addressed to assess the impact of repeated stress following acute cannabinoid exposure on behavior and corticostriatal brain physiology by assessing mice behavior, the concentration of endocannabinoid and endocannabinoid‐like molecules and changes in the transcriptome. Results: Stressed animals urinated frequently; showed exacerbated scratching activity, lower striatal N ‐arachidonylethanolamine (AEA) levels and higher cortical expression of cholinergic receptor nicotinic alpha 6. The cannabinoid agonist WIN55212.2 diminished locomotor activity while the inverse agonist increased the distance travelled in the center of the open field. Upon CB1 activation, N ‐oleoylethanolamide and N ‐palmitoylethanolamide, two AEA congeners that do not interact directly with cannabinoid receptors, were enhanced in the striatum. The co‐administration with both cannabinoids induced an up‐regulation of striatal FK506 binding protein 5. The inverse agonist in controls reversed the effects of WIN55212.2 on motor activity. When Rimonabant was injected under stress, the cortical levels of 2‐arachidonoylglycerol were maximum. The agonist and the antagonist influenced the cortical expression of cholinergic receptor nicotinic alpha 6 and serotonin transporter neurotransmitter type 4 in opposite directions, while their co‐administration tended to produce a null effect under stress. Conclusions: The endocannabinoid system had a direct effect on serotoninergic neurotransmission and glucocorticoid signaling. Cholinergic receptor nicotinic alpha‐6 was shown to be deregulated in response to stress and following synthetic cannabinoid drugs thus could confer vulnerability to cannabis addiction and psychosis. Targeting the receptors of endocannabinoids and endocannabinoid‐like mediators might be a valuable option for treating stress‐related neuropsychiatric symptoms.